Estudo do transporte de oligopeptídeos em Aeromonas hydrophila e comparação com outras espécies do gênero - Cattani, Fernanda (My University, 2014)
The oligopeptide transport system (Opp system) is involved in different aspects of bacterial physiology, including nutrition, intercellular communication, and factors associated with virulence. These ABC transporters are formed by an oligopeptide binding protein, a permease, and ATP-binding domain. Aeromonas are ubiquous aquatic Gram-negative bacteria associated with several human diseases, particularly gastrointestinal disorders. Now a day, A. hydrophila, A. sobria and A. caviae are considered as emerging pathogens by the WHO. In this context, the objective of the present study was to characterize the oligopeptide transport system of Aeromonas using several bioinformatic and molecular tools. The results showed that as in other Gram-negative bacteria, the opp genes of Aeromonas are organized in a single policistronic operon formed by five genes (oppA, oppB, oppC, oppD and oppF). The oppA gene and its corresponding periplasmic oligopeptide-binding protein (OppA) are highly conserved, even between different bacterial families. A. hydrophila OppA model exhibits a typical Venus flytrap structure, similar to the S. typhimurium model. Furthermore, the presence of the oppA gene was confirmed in all the Aeromonas strains evaluated. The OppA of several Aeromonas species were recognized by antibodies obtained against E. coli OppA, confirming the similarity between these proteins, and the expression of the oligopeptide binding protein in Aeromonas. The complete or partial sequencing of the gene oppA of different species of Aeromonas allowed confirming the high conservation of this gene, and corroborate previous phylogenetic data.
O sistema de transporte de oligopeptídios (sistema Opp) está envolvido em diferentes aspectos da fisiologia bacteriana, incluindo nutrição, comunicação intercelular e fatores associados com a virulência. Estes transportadores ABC são formados por uma proteína de ligação a oligopeptídios, uma permease e um domínio de ligação ao ATP. As Aeromonas são bactérias Gram-negativas aquáticas ubíquas associadas com várias doenças em humanos, especialmente, gastrenterites. Atualmente, A. hydrophila, A. sobria e A. caviae são consideradas como patogenos emergentes pela OMS. Neste contexto, o objetivo do presente trabalho foi caracterizar o sistema de transporte de oligopeptídios em Aeromonas utilizando para tanto diversas ferramentas bioinformáticas e moleculares. Os resultados mostraram que, assim como em outras bactérias Gram-negativas, os genes opp de Aeromonas encontram-se organizados em um único operon policistrônico formado por cinco genes (oppA, oppB, oppC, oppD e oppF). O gene oppA e a proteína periplásmica de ligação a oligopeptídios correspondente (OppA) são altamente conservados, mesmo entre bactérias de famílias distintas. O modelo da proteína OppA de A. hydrophila mostrou a estrutura típica Venus flytrap , semelhante ao modelo de S. typhimurium. Além disso, a presença do gene oppA foi confirmada em todas as linhagens avaliadas. A OppA de várias espécies de Aeromonas foram reconhecidas por anticorpos obtidos contra a OppA de E. coli, confirmando a similaridade entre estas proteínas, e a expressão da OppA em Aeromonas. O seqüenciamento completo ou parcial do gene oppA de diferentes espécies de Aeromonas permitiu confirmar a elevada conservação do mesmo, e corroborar dados filogenéticos prévios.
Keywords: MICROBIOLOGIA DE ALIMENTOS; Aeromonas; Sistema Opp; Proteína de ligação ao oligopeptídeo OppA; Aeromonas; Opp system; Oligopeptide-binding protein OppA